PENERAPAN METODE PEMBELAJARAN LISTENING TEAM UNTUK MENINGKATKAN MOTIVASI BELAJAR DI KELAS V SD - Bukit, Herawaty (Jurnal Dinamika Pendidikan, 2016)
ABSTRACTThis study aims to improve students motivation after learning performed using the methodof the Listening Team in the subject of Social Science, Class V of Elelemntary School,totaling 25 students. The data collection technique used is observation sheets andquestionnaires. This research was conducted in two cycles of the first cycle and the secondcycle through four stages: planning, action, observation / observation, and reflection. Theresults obtained that student motivation menglami significant improvement. It can be seenfrom the increase in average student motivation for each cycle, t the average score of hefirst cycle students motivation, namely 68,68. 16 students were motivated with a percentage(64%), 7 students were motivated enough by percentage (28 %), and 2 students are notmotivated by the percentage (8%) and an increase in the second cycle is the average scoreof student motivation 78.08 i.e, 24 students were motivated by the percentage (96%), onlyone of the students was sufficiently motivated with percentage (4%) and no student wasmotivated with percentage (0%). The results of the questionnaire distributed to studentsalso increased, namely on the initial conditions before action there were only three studentswho have learnt high motivation with a percentage of 12% and thereafter Learning MethodsListening Team increased with the data in the first cycle of 10 students who have themotivation to learn with a high percentage of 40% and the second cycle of 23 students whohave high motivation to learn with the percentage of 92%. It can be concluded that the useof learning methods Listening Team can increase students motivation.Keywords: Methods, Learning, Listening Team Motivation.ABSTRAKPenelitian ini bertujuan untuk meningkatan motivasi belajar siswa setelah dilakukanpembelajaran menggunakan Metode Listening Team Pada Mata Pelajaran IPS Di Kelas VSD, yang berjumlah 25 orang siswa. Teknik pengumpulan data yang digunakan adalahmenggunakan lembar observasi dan angket. Penelitian ini dilakukan dalam dua siklus yaitusiklus I dan siklus II yang melalui 4 tahap yaitu perencanaan, pelaksanaan tindakan,pengamatan/observasi, dan refleksi. Hasil penelitian yang diperoleh bahwa motivasi belajarsiswa menglami peningkatan yang signifikan. Hal ini dapat dilihat dari peningkatan rataratamotivasi belajar siswa untuk tiap siklus, pada siklus I skor rata-rata motivasi belajarsiswa 68,68 yaitu 16 orang siswa termotivasi dengan persentase (64%), 7 orang siswacukup termotivasi dengan persentase (28%), dan 2 orang siswa tidak termotivasi denganpersentase (8%) dan terjadi peningkatan pada siklus II yaitu dengan skor rata-rata motivasibelajar siswa 78,08 yaitu 24 orang siswa termotivasi dengan persentase (96%), 1 orangsiswa cukup termotivasi dengan persentasse (4%) dan tidak ada siswa yang tidaktermotivasi denganpersentase (0%). Hasil penelitian dari angket yang dibagikan pada siswajuga mengalami peningkatan yaitu pada kondisi awal sebelum tindakan hanya ada 3 siswayang memiliki motivasi belajar tinggi dengan persentase 12% dan setelah dilaksanakanMetode Pembelajaran Listening Team mengalami peningkatan dengan data pada siklus I10 siswa yang memiliki motivasi belajar tinggi dengan persentase 40% dan pada siklus II23 siswa yang memiliki motivasi belajar tinggi dengan persentase 92%. Dengan demikiandapat disimpulkan bahwa penggunaan metode pembelajaran Listening Team dapatmeningkatkan motivasi belajar siswa.Kata kunci: Metode, pembelajaran, Listening Team Motivasi